Dramatic enhancement of intrinsic two-photon absorption in a conjugated porphyrin dimer - Karotki, A; Drobizhev, M; Dzenis, Y; Taylor, P; Anderson, H; Rebane, A (2004)
We report strong cooperative enhancement of simultaneous two-photon absorption cross section in a porphyrin dimer. The two-photon cross section, σ 2 = 6 × 10 -47 cm 4s/photon, corresponds to a 400-fold increase over the value measured for the monomer, and is one of the largest ever obtained for organic chromophore of similar size.